ICT, public administration and democracy in the coming decade - Meijer, Albert, 1967-; Bannister, Frank (Associate Professor (Statistics)); Thaens, Marcel (Innovation and the public sector, 2013)
The physicist Neils Bohr allegedly wrote that "Prediction is very difficult, especially about the future". Many academics believe that serious scholars should never attempt to write about the future, but some awareness of the ways in which the future of e-government may evolve is needed if well-grounded long-term decisions about issues such as infrastructures, institutions and educational programs are to be made. In addition, future-oriented research is of the utmost importance for informed public debate about technological developments with far reaching societal implications. This book marks